The Thermoelectric Properties of Bismuth Telluride. (5th April 2019) - Witting, Ian T.; Chasapis, Thomas C.; Ricci, Francesco; Peters, Matthew; Heinz, Nicholas A.; Hautier, Geoffroy; Snyder, G. Jeffrey
Abstract: Bismuth telluride is the working material for most Peltier cooling devices and thermoelectric generators. This is because Bi2 Te3 (or more precisely its alloys with Sb2 Te3 for p‐type and Bi2 Se3 for n‐type material) has the highest thermoelectric figure of merit, zT, of any material around room temperature. Since thermoelectric technology will be greatly enhanced by improving Bi2 Te3 or finding a superior material, this review aims to identify and quantify the key material properties that make Bi2 Te3 such a good thermoelectric. The large zT can be traced to the high band degeneracy, low effective mass, high carrier mobility, and relatively low lattice thermal conductivity, which all contribute to its remarkably high thermoelectric quality factor. Using literature data augmented with newer results, these material parameters are quantified, giving clear insight into the tailoring of the electronic band structure of Bi2 Te3 by alloying, or reducing thermal conductivity by nanostructuring. For example, this analysis clearly shows that the minority carrier excitation across the small bandgap significantly limits the thermoelectric performance of Bi2 Te3, even at room temperature, showing that larger bandgap alloys are needed for higher temperature operation. Such effective material parameters can also be used for benchmarking future improvements in Bi2 Te3 or new replacement materials. Abstract : The material properties underlying the exceptional thermoelectric performance of bismuth telluride are reviewed and compared with other notable materials. Using literature data and recent results, key parameters are identified to give insight into band structure engineering through alloying and thermal conductivity reduction by nanostructuring. Transport modeling is used to quantify these parameters and illustrate performance limitations.